WHISTLEBLOWER SYSTEM IN PREVENTING AND HANDLING OF SEXUAL VIOLENCE IN THE WORKPLACE IN INDONESIA: A CROSS-SECTIONAL STUDY - Noer, Khaerul Umam (Gapenas Publisher, 2024)
Sexual violence in the workplace is a significant issue, with over 30% of Indonesian workers experiencing or witnessing incidents, primarily affecting women. The Minister of Manpower's Decree 88/2023 is a crucial governmental measure designed to prevent and combat sexual violence in the workplace. This regulation requires organizations to formulate clear strategies for the preventing and handling of sexual violence in the workplace. By conducting qualitative research in 15 private companies, this study shows why it is important for companies to have a whistleblower system to prevent and address sexual violence in the workplace. This study investigates the implementation of whistleblower strategies by corporations, focusing on the strategic function of whistleblowers in mitigating and confronting sexual violence in the workplace and the impact of this system on fostering a secure work culture. Research shows that the repercussions of sexual violence on victims are significant, resulting in psychological suffer, physical health complications, and heightened stress levels. It also impacts the workplace environment, resulting in distrust, discontent, and increased employee turnover rates. Whistleblowers play a crucial role in preventing workplace sexual violence by providing a secure reporting method for employees. They ensure anonymity, allowing them to disclose their experiences without fear of repercussions. This approach fosters transparency, allowing offenders to reveal their actions at any time, changing power dynamics and preventing financial losses and reduced productivity. The effectiveness of a whistleblower system depends on the company's design and execution, which must be easily accessible to all employees. At the same time, whistleblower system also helps mitigate reputational risks and legal costs, especially with workplace sexual violence incidents